A Feminist Reading of Italy's North–South Dualism in the Wake of COVID-19. Issue 1 (3rd April 2021) - Corsi, Marcella; Aloè, Erica; Zacchia, Giulia
ABSTRACT: Italy has been hit hard by the COVID-19 pandemic. According to official data by the Italian National Institute of Health (as of July 22, 2020), more than 34, 000 patients, mostly elderly men, have died of COVID-19. The majority of these deaths (82 percent) are concentrated in the Northern regions. This study investigates Italy's North–South dichotomy, exploring differences in social norms and family habits among Italian regions from a feminist perspective. Relying on time-use data, it analyzes whether family roles have protected elderly people from the pandemic in the South as compared to the North. The paper emphasizes the need to recognize the value of care and support unpaid care work performed by elderly people within and across households. Further, the paper argues for the need to consider the changing conditions of eldercare and contributes to the growing debate about its quality in Italy and elsewhere. HIGHLIGHTS Care of and by the elderly has become a new feature of North–South dualism in social norms in Italy. North vs. South response to the pandemic reflects differences in terms of caring spirits. Differences in family structures may explain regional differences in severity of elderly mortality from COVID-19. The need to recognize the value of unpaid work has become urgent in the wake of the pandemic. Attention must be devoted to the intangible aspects of intrahousehold care practices.